Identification of the viral sequence required for the generation of recovered avian sarcoma viruses and characterization of a series of replication-defective recovered avian sarcoma viruses. - Wang, L H (1984)
The ability of transformation-defective deletion mutants of Schmidt-Ruppin Rous sarcoma virus to induce tumors and generate recovered sarcoma viruses (rASVs) was correlated with the partial src sequences retained in the transformation-defective viral genomes. Since all the transformation-defective viruses that were capable of generating rASVs retained a portion of the 3' src sequence, regardless of the extent of the 5' src deletion, and those lacking the 3' src were unable to generate rASVs, it appears that the 3', but most likely not the 5', src sequence retained in the transformation-defective viral genome is essential for rASV formation. However, rASVs derived from a particular mutant, td109, which retained a portion of the 3' src sequence, but lacked most (if not all) of the 5' src sequence, were all found to be defective in replication. Analyses of the genomic sequences of 13 isolates of td109-derived rASVs revealed that they contained various deletions in viral envelope (env), polymerase (pol), and structural protein (gag) genes. Ten isolates of rASVs contained env deletions. One isolate (rASV3812) contained a deletion of env and the 3' half of pol, and one isolate (rASV398) contained a deletion of env and pol. The one with the most extensive deletion (rASV374) had a deletion from the p12-coding sequence through pol and env. In addition, the 5' src region of td109-derived rASVs were heterogeneous. Among the 7 isolates analyzed in detail, one isolate of rASV had a small deletion of the 5' src sequence, whereas three other isolates contained extra new sequences upstream from src. Both env- and env- pol- rASVs were capable of directing the synthesis of precursor and mature gag proteins in the infected nonproducer cells. We attribute the deletions in the replication-defective rASVs to the possibility that the 5' recombination site between the td109 and c-src sequence, involved regions of only partial homology due to lack of sufficient 5' src sequence in the td109 genome for homologous recombination. A model of recombination between the viral genome and the c-src sequence is proposed to account for the requirement of the 3' src sequence and the basis for the generation of deletions in td109-derived rASVs.